Observation of the pathogenicity of Metarhizium anisopliae in Nasutitermes sp. soldiers - GUTIÉRREZ-G., ANA ISABEL; SALDARRIAGA-O., YAMILLÉ (Revista Colombiana de Entomología, 2004)
Soldiers of Nasutitermes sp., pests of Cordia alliodora (Ruiz & Pav.) Oken, family Boraginaceae, a tree of great economic and medicinal importance were inoculated in vitro with the fungus Metarhizium anisopliae (Metsch.) Sor. impregnated on canvases or filter paper at a concentration of 1x107 conidias/ml. Observations on the development of the fungal infection were made with a light microscope. The development of the fungus was observed on mounted slides with lactophenol blue, using a clarifying technique with KOH solutions at 5, 10, 15, and 20%. infected termites died I to 3 days post-inoculation, the fungus penetrating the cuticle at 24 hours, colonizing the fat tissue at 72 hours, and invading the internal organs (gut) after 72 hours of infection. At 120 hours a white compact mass of conidiophores began to emerge from the cuticle at the intersegmental regions of the ventral surface (legs, thorax) and mouthparts of the insects. After 144 hours of inoculation, the mycelia changed to green, and at 192 hours the mycelia turned dark and powdery when the termite body was totally invaded.